HISTORICAL SIGNIFICANCE OF THE CRIMINAL CASE’S NO. 31 MATERIALS DEALING WITH THE DESTRUCTION OF THE AUDRINI VILLAGE’S INHABITANTS BY NAZI GERMANY’S OCCUPATION POWER - Malahovskis, Vladislavs (Administrative and Criminal Justice, 2019)
Audrini has been an administrative center in Rezekne region since 1990. Before the Second World War, Audrini was one of the villages in Makaseni rural municipality populated by old believers. The tragedy of Audrini is destruction of Audrini inhabitants by Nazi German occupation institutions (22.12.1941. – 01.04.1942). Escaped prisoners of Red Army were hidden in the village. The Nazis burnt down village buildings. In the Ancupanu hills, arrested inhabitants of the village were shot; 30 men – inhabitants of Audrini – were publicly shot at the Marketplace in Rezekne. The punishment action was done in accordance with the German Security Police Commander’s orders; in the action local collaborators – Rezekne and Malta police officers – participated. Criminal case No 31 was initiated on August 5th, 1964. In 1965, an open trial in Riga was held (11.10.1965.–10.30.1965), where six former German police officers were accused of Audrini people killing. Criminal case No.31 consists of 37 huge volumes. Basically, there are three kinds of documents: 1) protocols of witnesses’ testimonies; 2) Rezekne region police reports and correspondence with higher instances; 3) the documents related to criminal investigation process. The paper reveals the reasons for the initiation of the Audrini village’s criminal case, the content of the documents available in the criminal case. The reasons for destruction of Audrini inhabitants are stated as well as the revealing of Audrini tragedy in Soviet propaganda and arts after the completion of criminal proceedings.